"Mi Historia Familiar Es Sencilla" (My Family History Is Simple)": Testimonio in the New Latino Diaspora. Issue 1 (2nd January 2018) - McClure, Greg; Fitts, Shanan
ABSTRACT: In this paper, we share the testimonio of Santana, an immigrant from rural México, who explained the ways that she navigates her life and raises her children as a Latina immigrant woman here in the southeastern United States. Our inquiry is guided by analysis of ethnographic interviews conducted with Santana over a period of three years. We argue that Santana saw these interviews as an opportunity to share testimonios —embodied life stories that bear witness to a history of social injustice. Testimonio centralizes marginalized knowledge and documents a collective experience of injustice via an individual narrative. Santana's testimonio underscores the complex ways that Latina migrants draw from embodied experiences to resist oppression and sobrevivir, a verb that implies not only enduring, but moving forward with knowledge, power, self-confidence, and creativity. We argue that her testimonio disrupts the power relations embedded in the traditional hierarchy between the researcher and the research participant.